Healthy Native Youth: Improving Access to Effective, Culturally-Relevant Sexual Health Curricula - Craig Rushing, Stephanie; Stephens, David; Shegog, Ross; Torres, Jennifer; Gorman, Gwenda; Jessen, Cornelia; Gaston, Amanda; Williamson, Jennifer; Tingey, Lauren; Lee, Crystal; Apostolou, Andria; Kaufman, Carol; et al. (Frontiers in Public Health, 2018)
Tribal health educators across the United States have found it challenging to locate engaging, culturally-relevant sexual health curricula for American Indian and Alaska Native (AI/AN) youth. Healthy Native Youth is a new online resource that provides a “one-stop-shop” for tribal health advocates to access age-appropriate curricula. The site was designed by a team of advisers representing a diverse group of tribal communities, using a collaborative planning process. The website content and navigation was then refined through usability testing with the target audience. The portal allows users to filter and compare curricula on multiple dimensions, including: age, delivery setting, duration, cost, and evidence of effectiveness, to determine best-fit. It includes all materials needed for implementation free-of-charge, including: facilitator training tools, lesson plans, materials to support participant marketing and recruitment, information about each program's cultural relevance, evaluation methods and findings, and references to publications and reports. The website currently includes mCircle of Life, Native It's Your Game, Native STAND, Native VOICES, and Safe in the Village, among others. Since its launch in August 2016, the site has had over 31,000 page views in all 50 States. The Healthy Native Youth portal provides educators in rural communities a promising new tool to support the dissemination and implementation of evidence-based health curricula in geographically-disbursed AI/AN communities. Lessons learned during the design and dissemination of the Healthy Native Youth website may be of value to other Indigenous populations interested in our approach and our findings.